The potential therapeutic value of the natural plant compounds matrine and oxymatrine in cardiovascular diseases - Chen, Shanjiang; Wu, Shu; Lin, Bin (Frontiers in Cardiovascular Medicine, 2024)
Matrine (MT) and Oxymatrine (OMT) are two natural alkaloids derived from plants. These bioactive compounds are notable for their diverse pharmacological effects and have been extensively studied and recognized in the treatment of cardiovascular diseases in recent years. The cardioprotective effects of MT and OMT involve multiple aspects, primarily including antioxidative stress, anti-inflammatory actions, anti-atherosclerosis, restoration of vascular function, and inhibition of cardiac remodeling and failure. Clinical pharmacology research has identified numerous novel molecular mechanisms of OMT and MT, such as JAK/STAT, Nrf2/HO-1, PI3K/AKT, TGF-β1/Smad, and Notch pathways, providing new evidence supporting their promising therapeutic potential against cardiovascular diseases. Thus, this review aims to investigate the potential applications of MT and OMT in treating cardiovascular diseases, encompassing their mechanisms, efficacy, and safety, confirming their promise as lead compounds in anti-cardiovascular disease drug development.